A Systematic Review of the Inclusion (or Exclusion) of Women in HIV Research: From Clinical Studies of Antiretrovirals and Vaccines to Cure Strategies. (1st February 2016) - Curno, Mirjam J.; Rossi, Samuela; Hodges-Mameletzis, Ioannis; Johnston, Rowena; Price, Matt A.; Heidari, Shirin
Abstract : Introduction: The effect of clinical interventions can differ because of sex/gender. Studies have shown that women are often under-represented in medical research. The aim of this systematic literature review was to characterize women's participation in HIV clinical studies of antiretroviral drugs (ARV), prophylactic vaccines (VAX), and curative strategies (CURE). Methods: Systematic PubMed searches were conducted to identify ARV, VAX, and CURE studies. Data were extracted on the number of women, date of publication, sources of funding, country of study, and trial phase. Correlates of female participation were assessed. Results: Women represented a median of 19.2% participants in ARV studies (387), 38.1% in VAX studies (53), and 11.1% in CURE studies (104). Funding source was not correlated with the proportion of female participants in VAX and CURE studies but was for ARV studies ( P = 0.03). ARV trials funded by private noncommercial sources had the highest proportion of women, whereas publicly funded trials had the lowest female participation (median 16.7%). The median proportion of women in ARV trials that were fully or partially funded by the National Institutes of Health was significantly lower than the median in trials funded by other sources (19.6% vs. 22.3%, P = 0.001). Conclusions: Although women comprise nearly half of people living with HIV, they continue to be under-represented in clinical studies. Despite federal policies that have been established to address this, our study shows that publicly funded ARV trials recruit even fewer women than other trials. There is an urgent need to ensure that HIV clinical studies consider sex/gender dimensions. Abstract : Supplemental Digital Content is Available in the Text.